Introduction to Special Issue on Health Financing in East and Southern Africa - Schneider, Pia; Yazbeck, Abdo S.; Lindelow, Magnus (Taylor and Francis, 2019)
This special issue on health financing in East and Sothern Africa comes at an opportune time. Economic growth in the region is contributing to a changing lifestyle and an increasing burden of noncommunicable diseases, such as diabetes, which are costlier to treat. Coupled with the unfinished health agenda of communicable diseases and maternal and child health, demand for health care is increasing rapidly and putting financial pressure on governments. A risky response in a resource-constrained setting is governments reallocating funds away from the poor to more expensive specialist and tertiary care. Another risky response relates to ways of raising additional revenues, especially in countries where health facilities already charge user fees in the absence of prepayment. Relatively poor patients who pay fees when seeking care may have to sell assets and incur debts, which may push them into poverty or deeper into poverty. Protecting households against falling into poverty and ensuring access to essential health services are thus top priorities for governments committed to universal health coverage (UHC) in the region. Achieving this objective requires solving several pertinent problems.